BUSINESS ADMINISTRATION STUDENTS’ ANXIETY IN SPEAKING SKILL PRACTICE - Fu'ad Sholikhi (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2021)
Speaking anxiety is a feeling of fear about what is to come when speaking. Students' conditions may trigger excessive anxiety that can make students struggle to move and speak in front of the public. The purposes of this study are to determine the level of business administration students’ speaking anxiety at UNISBA Blitar and to investigate the most dominant speaking anxiety in ESP class. This study utilizes descriptive quantitative with thirty-three questionnaires as a research instrument distributed to second-semester of Business Administration students of UNISBA. The questionnaires were then analyzed and categorized into responses and speaking anxiety levels. Once the data of Business Administration students’ speaking anxiety level had been collected, the researcher calculated the average and the percentage of the data and categorized them into three types of speaking anxiety in the classroom. In addition, the researcher utilized a five-point Likert scale, discovering two students experienced an anxiety level, three students experienced a relaxed level, and twenty-five students were mildly anxious. The most dominant speaking anxiety type was Test Anxiety with a total of 450 items (45.45%), followed by Communication Apprehension (33.34%), and students’ fear of negative evaluation as the lowest (21.21%). In the end, the future researcher interested in conducting similar research about speaking anxiety is expected to use a different number of participants and research methodology to enrich the knowledge about speaking anxiety in higher education.